PEREMPUAN SEBAGAI AGEN PERUBAHAN: KONTRIBUSI DALAM INDUSTRI RUMPUT LAUT DAN KESEJAHTERAAN KELUARGA - Nengsi, Sri; Mukramin, Sam'un; Amin, Sulvahrul (Gapenas Publisher, 2024)
The role of women in the seaweed industry in Bonto Jai Village, Bissappu District, Bantaeng Regency, and its impact on improving the welfare of the local community. The method used is a qualitative paradigm with in-depth interview techniques, participatory observation. The results of the study show that women play an important role in the entire seaweed production process, from planting, maintenance, to processing and marketing. This role not only makes a significant contribution to the family economy but also empowers women socially and economically. The involvement of women in the seaweed industry has increased household income, strengthened women's positions in decision-making, and increased their access to education and health services. Therefore, women's empowerment in the seaweed industry in Bonto Jai Village has proven to be an effective strategy in efforts to improve the welfare of the community as a whole. Support from the government and related institutions is needed to strengthen and expand the positive impact of women's roles